Synergetic Effect of Sodium Borohydride Addition in Ammonia Borane Hydrolysis Reaction Mechanism and Kinetics - Figen, A. Kanturk; Tasci, K.; Filiz, B. Coskuner (PLEIADES PUBLISHING LTD, 2018)
Synergetic effect of sodium borohydride (NaBH4) addition to ammonia borane (NH3BH3) hydrolysis reaction had been studied and iron-borate (FeB) was used to catalyze the reaction. Hydrogen generation performance of the hydrolysis reactions was compared for three different operating conditions: (1) in the presence of NaBH4 with FeB catalyst, (2) with FeB without NaBH4 addition and (3) in the presence of NaBH4 without FeB. It was found that addition of NaBH4 to the NH3BH3 hydrolysis reaction catalyzed by FeB resulted in the synergetic effect (synergetic factor (SF) > 0) and improved the hydrogen generation performance. Kinetic analysis showed that NaBH4 addition decreases the activation energy (E (a)) from 52.11 +/- 0.85 to 27.19 +/- 0.44 kJ/mol. Simulation of hydrolysis kinetics curves indicated that addition of NaBH4 (the mole fraction of NaBH4 added to NH3BH3 is (1)) changed the three-dimensional diffusion mechanism to the one-dimensional one and brought on better hydrolysis properties in terms of higher hydrogen generation rate and lower induction time.
Keywords: ammonia borane; synergetic effect; sodium borohydride; hydrogen; nucleation-growth model; METAL-ORGANIC FRAMEWORKS; HYDROGEN GENERATION; GRAPHENE OXIDE; NANOPARTICLES; CATALYST; DEHYDROGENATION; BEHAVIORS; HYDRIDES; PORES; Chemistry